Artemchuk V. Properties of layered electrolytic alloys Fe-P, received the Software electrolysis. - Артемчук, В.В. (Problems of Tribology, 2014)
The article deals with one of the promising areas of repair production, namely the restoration of components, in particular layered coatings with desired properties. A study evaluating the efficacy of electrolytic iron-phosphorus alloys, the definition of a rational component content in the alloy layers deposited coatings. The purpose of this study is to determine the properties and performance of electrolytic iron-based alloys, the definition of rational content of the components in the alloy layers renewable coatings. The problem of improving the reliability and lifetime of the details are important and relevant not only for rail transport, but also for any vehicle. One of the priorities of industry output also remains the repair of railway on the current level. Use of the electrolysis has broad capabilities that allow for high-quality restoration coatings and to some extent affect the structure and chemical composition of alloys by selective discharge of electrolyte components, thereby adjusting layer properties only coverage. During the research it was found that the friction of the alloy Fe-P, as well as many other materials, is a combination of different mechanisms of wear. Wear resistance of the resulting software Fe-P alloy at about 2.8 times higher in dry friction and is 2.3 times the limit when compared to steel 45; 1.18 times compared to similar coatings obtained in stationary conditions; 2 times increase from electrolytic iron.